PENGGUNAAN MEDIA KANTONG NILAI (WORTH BAG) UNTUK MENINGKATKAN PEMAHAMAN PENJUMLAHAN DENGAN TEKNIK MENYIMPAN - Nanik Ulfa; Melani Albar; Fatimatuz Zahro (Universitas Islam Raden Rahmat Malang, 2024)
This research is motivated by the teaching and learning activities at MI Al Adroiyah Krebet which are still minimal in the use of learning media, resulting in low student understanding of teacher explanations, especially in learning mathematics in addition material. The purpose of this research is to improve students' understanding. The type of research used is Classroom Action Research (PTK) with a mixed approach approach. The results of the study show that through the use of pocket value media can improve students' understanding of addition which is characterized by an increase in student learning outcomes. In the evaluation of the first cycle, the average value has reached 68.55 and the completeness level is 60%. In the post-test cycle II, the average student score was 79.55 and the student completeness level had reached 80%. In cycle II the average value of students increased by 10.88. While the percentage increased by 20%. This shows that learning with value pocket media has gone well and has increased as expected.